Impact of dietary fat on the development of non-alcoholic fatty liver disease in Ldlr−/− mice. Issue 1 (18th August 2015) - Jump, Donald B.; Depner, Christopher M.; Tripathy, Sasmita; Lytle, Kelli A.
Abstract : The prevalence of non-alcoholic fatty liver disease (NAFLD) has increased in parallel with central obesity and is now the most common chronic liver disease in developed countries. NAFLD is defined as excessive accumulation of lipid in the liver, i.e. hepatosteatosis. The severity of NAFLD ranges from simple fatty liver (steatosis) to non-alcoholic steatohepatitis (NASH). Simple steatosis is relatively benign until it progresses to NASH, which is characterised by hepatic injury, inflammation, oxidative stress and fibrosis. Hepatic fibrosis is a risk factor for cirrhosis and primary hepatocellular carcinoma. Our studies have focused on the impact of diet on the onset and progression of NASH. We developed a mouse model of NASH by feeding Ldlr −/− mice a western diet (WD), a diet moderately high in saturated and trans-fat, sucrose and cholesterol. The WD induced a NASH phenotype in Ldlr −/− mice that recapitulates many of the clinical features of human NASH. We also assessed the capacity of the dietary n- 3 PUFA, i.e. EPA (20 : 5, n- 3) and DHA (22 : 6, n- 3), to prevent WD-induced NASH in Ldlr −/− mice. Histologic, transcriptomic, lipidomic and metabolomic analyses established that DHA was equal or superior to EPA at attenuating WD-induced dyslipidemia and hepatic injury, inflammation, oxidative stress and fibrosis. Dietary n- 3 PUFA, however, had no significant effect on WD-induced changes in body weight, body fat or blood glucose. These studies provide a molecular and metabolic basis for understanding the strengths and weaknesses of using dietary n- 3 PUFA to prevent NASH in human subjects.